PENGARUH KONVERGENSI IFRS, ASIMETRI INFORMASI DAN KEPEMILIKAN MANAJERIAL TERHADAP INCOME SMOOTHING PADA PERBANKAN YANG TERDAFTAR DI BEI 2010-2014 - JANNAH, ZAHROTUL (Jurnal Akuntansi AKUNESA, 2016)
Income smoothing is a common phenomenon that occurs as management efforts to reduce fluctuations in reported earnings. Based on the recapitulation of the calculation of income smoothing on the financial sector, banks have the highest income smoothing indication conduct than other financial sectors. Jimbalvo (1996) said that the process of delivering information to income investor is influenced by accounting standards and information asymmetry,Other factors is managerial ownership. Hence, influence of IFRS convergence, information asymmetry and managerial ownership to  income smoothing. This research used 14  Banks company  listed in the Indonesia Stock Exchange, which are selected using purposive sampling during the research period 2010 until 2014. Data were analyzed using multiple regression with the help of the program SPSS 21 for windows. Based on test results concluded that IFRS convergence and information asymmetry  variable has no significant effect on income smoothing and Managerial ownership has positive significant effect on income smoothing. Keywords: IFRS Convergence, Information Asymmetry, Managerial Ownership, Income Smoothing